2022
DOI: 10.1038/s41398-022-02094-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of the immune system in posttraumatic stress disorder

Abstract: Posttraumatic stress disorder (PTSD) develops in a subset of individuals upon exposure to traumatic stress. In addition to well-defined psychological and behavioral symptoms, some individuals with PTSD also exhibit elevated concentrations of inflammatory markers, including C-reactive protein, interleukin-6, and tumor necrosis factor-α. Moreover, PTSD is often co-morbid with immune-related conditions, such as cardiometabolic and autoimmune disorders. Numerous factors, including lifetime trauma burden, biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 242 publications
0
21
0
Order By: Relevance
“…Further support for our findings comes from Universal Protein Knowledgebase functional annotation. The molecular function and biological process data show that several genes are implicated in each of several broad mechanisms, including the immune response or inflammation, apoptosis, and energy metabolism, which have been implicated in PTSD (Chen et al, 2020; Katrinli et al, 2022; Somvanshi et al, 2019). Several of the genes identified, and by extension, their associated pathways, are thought to be broadly implicated in the development of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for our findings comes from Universal Protein Knowledgebase functional annotation. The molecular function and biological process data show that several genes are implicated in each of several broad mechanisms, including the immune response or inflammation, apoptosis, and energy metabolism, which have been implicated in PTSD (Chen et al, 2020; Katrinli et al, 2022; Somvanshi et al, 2019). Several of the genes identified, and by extension, their associated pathways, are thought to be broadly implicated in the development of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Exposures to neurotoxicants that were present during the GW have been associated with elevations in various markers of inflammation in murine species (Ashbrook et al., 2018; Koo et al., 2018; Locker et al., 2017; Miller et al., 2018). Elevated inflammatory activity has also been associated with PTSD and may play a significant role in its pathogenesis (Hori & Kim, 2019; Katrinli et al., 2022). Consistent with this theory, a recent meta‐analysis of cross‐sectional studies showed that C‐reactive protein (CRP), interleukin 6, and tumor necrosis factor‐α were significantly elevated in patients with PTSD in comparison with healthy controls (Yang & Jiang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Suggested disorders associated with anxiety include a transitory rise in salivary cortisol and reactive oxygen species in the saliva [ 55 ]. In the same context, grief is associated with dysregulation of the immune function resulting in the elevation in inflammation-related health problems [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ], one of which is recurrent oral ulcers [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%